2016
DOI: 10.1097/wnr.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of miR-132, miR-134, and miR-485 in rat primary motor cortex during transhemispheric functional reorganization after contralateral seventh cervical spinal nerve root transfer following brachial plexus avulsion injuries

Abstract: The transfer of a contralateral healthy seventh cervical spinal nerve root (cC7) to the recipient nerve in the injured side is considered a promising procedure for restoration of the physiological functions of an injured hand after brachial plexus root avulsion injury (BPAI). Growing evidence shows that transhemispheric cortical reorganization plays an important role in the functional recovery of the injured arm after cC7 nerve transfer surgery. However, the molecular mechanism underlying the transhemispheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Numerous studies have suggested that miR-142-5p and miR-134-5p are closely related to nervous system diseases and peripheral nerve injury [33][34][35][36][37][38] . Previous studies have con rmed that MiR-142-5p plays a role in protecting nerves and promoting nerve repair by regulating the viability and apoptosis of neuronal cells during nerve injury repair 24 .…”
Section: Mir-134-5p Promotes the Proliferation And Migration Of Schwa...mentioning
confidence: 99%
“…Numerous studies have suggested that miR-142-5p and miR-134-5p are closely related to nervous system diseases and peripheral nerve injury [33][34][35][36][37][38] . Previous studies have con rmed that MiR-142-5p plays a role in protecting nerves and promoting nerve repair by regulating the viability and apoptosis of neuronal cells during nerve injury repair 24 .…”
Section: Mir-134-5p Promotes the Proliferation And Migration Of Schwa...mentioning
confidence: 99%
“…Factors participating in the network of motor cortical remodelling after BPRA display dynamic changes. Major microRNAs (miRNAs/miRs) distributed in the motor cortex, such as miR-101-3p, miR-132, miR-134, miR-137-3p and miR-485, play vital roles in regulating neural plasticity and transhemispheric functional reorganization dendrite morphology, spontaneous synaptic responses and transmitter release after cervical spinal nerve root transfer following BPA injury [61,81,86]. Functional MRI studies revealed that the levels of proinflammatory cytokines, such as interleukin (IL)-1β, IL-6, tumour necrosis factor α (TNF-α), are important mediators in the neural plasticity and transhemispheric functional reorganization [33,36,57,98].…”
Section: Brain Changesmentioning
confidence: 99%
“…miRNAs exert a significant effect on oncogenesis (Piotrowski et al, 2021;Tan et al, 2021). At present, miRNA expression has been observed in various tumours and is closely related to tumour growth (Jiang et al, 2016), metastasis (Wang et al, 2016), angiogenesis (Lu et al, 2015), and other malignant biological characteristics; thus, it is considered an indispensable regulator of tumorigenesis. Therefore, miRNAs detection is beneficial for early clinical diagnosis; moreover, modulating their expression in tumours may have potential clinical values.…”
Section: Introductionmentioning
confidence: 99%